2021
DOI: 10.1115/1.4051654
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of an oil-lubricated journal bearing using bionic-textures fused micro-pockets

Abstract: This article investigates the static and dynamic performances of bionic-textures fused micro-pocketed journal bearing considering cavitation. The new bionic textures placed inside the micro-pocket towards the trailing side has been conceived inspired from the skins of freshwater fish. The mass conservation satisfying partial differential lubrication equations for the static and dynamic pressures are discretized using finite volume method (FVM) followed by simultaneous solution of the system equations using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Many numerical methods have been used to solve the Reynolds equation. Such as the finite difference method (FDM), finite element method and finite volume method (Lugt and Morales-Espejel, 2011; Habchi et al , 2007; Pattnayak et al , 2002; Gengyuan et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical methods have been used to solve the Reynolds equation. Such as the finite difference method (FDM), finite element method and finite volume method (Lugt and Morales-Espejel, 2011; Habchi et al , 2007; Pattnayak et al , 2002; Gengyuan et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years to explore and improve the tribodynamic performances of generic concentrated contacts such as vibration, film thickness and friction coefficient/torque etc., different surface textures have been employed. The surface textures comprising of the presence of nano/micro geometries such as spherical/ellipsoidal, [4][5][6][7][8][9][10][11][12][13][14][15] triangular dimples, 16 micro-grooves/pockets, [17][18][19][20][21][22] and bionic shapes 17,23,24 on the mating surfaces have widely been employed to understand their roles on the performances. Based on the numerical 7,17,18,23 and experimental [4][5][6][7][8][9][10][11][12][13][14][15][16][19][20][21][22][24][25][26] investigations performed with textured lubricated concentrated contacts, favorable results in terms of redu...…”
Section: Introductionmentioning
confidence: 99%
“…The surface textures comprising of the presence of nano/micro geometries such as spherical/ellipsoidal, 415 triangular dimples, 16 micro- grooves/pockets, 1722 and bionic shapes 17,23,24 on the mating surfaces have widely been employed to understand their roles on the performances. Based on the numerical 7,17,18,23 and experimental 416,1922,2426 investigations performed with textured lubricated concentrated contacts, favorable results in terms of reductions in temperature and frictional torque/ friction coefficient and increase in film thickness have been found. Literature review revealed that the geometries of tiny structures and their placing on the contacting surfaces (shape, size, position and orientation) along with their density have played great role on the tribo-performances of the concentrated contacts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been understood that when the plain runner surface interfaces with the textured bearing surface in the presence of lubricant at favorable operating parameters, numerous micro-hydrodynamic bearings get formed, which sustains the applied external load energy efficiently [15][16][17]. In addition to this, the micro/tiny geometries present in the texture act as innumerable lubricant reservoirs, which trap the wear debris and contaminants [18][19][20]. This mainly reduces three-body abrasion in the mixed and boundary lubrication regimes at the time of start and stop of runner/rotor.…”
Section: Introductionmentioning
confidence: 99%